2009
DOI: 10.1016/s1472-9792(09)70016-2
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis ftsH expression in response to stress and viability

Abstract: SUMMARY FtsH is an essential membrane bound protease that degrades integral membrane proteins as well as cytoplasmic proteins. We show that Mycobacterium tuberculosis (Mtb) ftsH expression levels are upregulated upon exposure to agents that produce reactive oxygen and nitrogen intermediates (ROI and RNI) and growth in macrophages. In partial support of this result is our observation that the Mtb merodiploid overexpressing ftsH shows increased resistance to ROI. ftsH transcripts levels are downregulated during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…For example, a recent report indicates that FtsZ is a substrate of FtsH protease in vitro 29 . Our preliminary data indicate that FtsZ levels are modulated in M. tuberculosis strains expressing altered levels of FtsH 30 . Presumably, FtsH and other unrecognized proteases, could act to reduce FtsZ levels.…”
Section: Resultsmentioning
confidence: 69%
“…For example, a recent report indicates that FtsZ is a substrate of FtsH protease in vitro 29 . Our preliminary data indicate that FtsZ levels are modulated in M. tuberculosis strains expressing altered levels of FtsH 30 . Presumably, FtsH and other unrecognized proteases, could act to reduce FtsZ levels.…”
Section: Resultsmentioning
confidence: 69%
“…A similar role was also suggested for FtsH when B. subtilis was subjected to environmental stress [46,47]. FtsH/HflB was also found to be involved in temperature and salt tolerance in B. subtilis, Lactococcus lactis, and Lactobacillus plantarum through degradation of denatured proteins [46,[48][49][50]. It is possible that either plant or insect response to phytoplasma infection leads to an increase of oxidative stress towards phytoplasma which could, in turn, induce modifications of ftsH expression to enhance protection.…”
Section: Discussionmentioning
confidence: 57%
“…Indeed, host-dependent expression could also be related to phytoplasma capability to respond to the stress imposed by the host-cell environment. In Mycobacterium tuberculosis, ftsH expression was upregulated upon exposure to agents producing reactive oxygen and nitrogen intermediates, and overexpression of ftsH in this bacterium increases resistance to reactive oxygen species and intermediates, while ftsH transcript levels are downregulated during the stationary phase and starvation [46]. A similar role was also suggested for FtsH when B. subtilis was subjected to environmental stress [46,47].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, some information can be gained by overexpression studies. Such work has shown that FstH appears to respond to oxidative stress and that it may regulate FtsZ levels and inhibit cell division (132), while the Rv2719c protein, which has some PG degradative activity, seems to regulate cell division by an indirect effect of altering the midcell location of the FtsZ ring (133).…”
Section: Pg Genes and Cell Divisionmentioning
confidence: 99%